HBV/HIV Coinfection: Impact on the Development and Clinical Treatment of Liver Diseases - Cheng, Zhimeng; Lin, Panpan; Cheng, Nansheng (Frontiers in Medicine, 2021)
Hepatitis B virus (HBV) infection is a common contributor to chronic hepatitis, liver cirrhosis, and hepatocellular carcinoma. Approximately 10% of people with human immunodeficiency virus (HIV) also have chronic HBV co-infection, owing to shared transmission routes. HIV/HBV coinfection accelerates the progression of chronic HBV to cirrhosis, end-stage liver disease, or hepatocellular carcinoma compared to chronic HBV mono-infection. HBV/HIV coinfection alters the natural history of hepatitis B and renders the antiviral treatment more complex. In this report, we conducted a critical review on the epidemiology, natural history, and pathogenesis of liver diseases related to HBV/HIV coinfection. We summarized the novel therapeutic options for these coinfected patients.